Asset management and international capital markets - Bessler, Wolfgang; Drobetz, Wolfgang; Adcock, Chris (Routledge, 2013)
This innovative volume comprises a selection of original research articles offering a broad perspective on various dimensions of asset management in an international capital market environment. The topics covered include risk management and asset pricing models for portfolio management, performance evaluation and performance measurement of equity mutual funds as well as the wide range of bond portfolio management issues. Asset Management and International Capital Markets offers interesting new insights into state-of-the-art asset pricing and asset management resea.